Berengeria Gil-Santana & Coletto-Silva, a junior synonym of Ectrichodiella Fracker & Bruner, with new records and taxonomic notes on Ectrichodiinae from Brazil, and with keys to Ectrichodiinae and Reduviinae genera of the New World (Hemiptera: Heteroptera: Reduviidae) - Gil-Santana, Hélcio R.; Baena, Manuel; Grillo, Horacio (Zootaxa, 2013)
Berengeria Gil-Santana & Coletto-Silva, 2005 is considered a junior synonym of Ectrichodiella Fracker & Bruner, 1924. Ectrichodiella minima (Valdés, 1910) and E. rafaeli (Gil-Santana & Coletto-Silva, 2005), new. comb. are redescribed. Tax-onomic notes on Brontostoma alboannulatum (Stål, 1860), B. discus (Burmeister, 1835), B. nanus Carpintero, 1980, B. rubrovenosum (Stål, 1860), and B. trux (Stål, 1859) are given. Brontostoma diringshofeni Gil-Santana & Baena, 2009, B. nanus, and Racelda robusta Bérenger & Gil-Santana, 2005 are recorded from Brazil for the first time. Keys to Ectricho-diinae and Reduviinae genera of the New World are presented.